2018
DOI: 10.1111/obr.12793
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and cardiometabolic disorders: a review of current evidence, genetic determinants and pathomechanisms

Abstract: Vitamin D deficiency has been implicated in the pathophysiology of cardiometabolic disorders including obesity, type 2 diabetes mellitus, cardiovascular diseases and polycystic ovary syndrome. Despite a large number of experimental and observational studies supporting a role for vitamin D in these pathologies, randomized controlled trials have reported little to no effect of vitamin D supplementation in the prevention or treatment of these disorders, although some results remain ambiguous. Polymorphisms in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 150 publications
2
45
0
1
Order By: Relevance
“…We found that severity of obesity was inversely related to vitamin D levels after controlling for age and sex. Similar to our results, current evidence suggests that greater obesity leads to lower 25-OH vit D levels, while the opposite relationship is generally not shown (27). There are many possible hypotheses to account for the lower 25-OH vit D concentrations in obese individuals (10,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 87%
“…We found that severity of obesity was inversely related to vitamin D levels after controlling for age and sex. Similar to our results, current evidence suggests that greater obesity leads to lower 25-OH vit D levels, while the opposite relationship is generally not shown (27). There are many possible hypotheses to account for the lower 25-OH vit D concentrations in obese individuals (10,(27)(28)(29).…”
Section: Discussionsupporting
confidence: 87%
“…The 25(OH)D3 is widely used in assessment of vitamin D status. 25(OH)D3 is converted in the liver to 1,25(OH)2D, which is the main ligand for VDR [29]. When 1,25(OH)2D binds to this complex, it leads to the transcription of several vitamin D-regulated genes [23].…”
Section: Discussionmentioning
confidence: 99%
“…Водночас систематичні аналізи результатів досліджень впливу саплементації вітаміну D при СПКЯ поки що не дають можливості стверджувати про її клінічний ефект [52]. Можливо, це пов'язано з поліморфізмом генів, що регулюють метаболічні ефекти вітаміну D, зокрема генним поліморфізмом рецептора вітаміну D білка, зв'язуючого вітамін D, та фермента 1-α-гідроксилази [52].…”
Section: роль вітаміну D в патогенезі спкя та його кардіометаболічнихunclassified